Peran Kepala Sekolah Sebagai Sarana Pendidikan Karakter Bagi Siswa - Handoko, Hanwar Priyo (Jurnal Dewantara, 2016)
Education is a conscious and deliberate effort to create an atmosphere of learning and the learning process so that learners are actively developing the potential for him to have the spiritual power of religion, self-control, personality, intelligence, character, and skills needed him, society, nation and state. In this study, the researchers focused on the role of the principal to the formation of national character in students. In this study the authors are interested in the role of school principals on the implementation of character education to students SMA Negeri 5 Metro. The purpose of character education to improve the quality of the process and outcomes of education that leads to the establishmen-Tukan person's character and noble character as a whole, an integrated, balanced, in accordance with the competency standards at any educational institution. Indicators of success can be seen character education program and students have properties such as: awareness, honesty, sincerity, simplicity, independence, care, freedom of action, precision, and commitment.